Power Demand Side Management Policy Incentive Process Dynamic Evolutionary Game Analysis - Zongyun SONG; Jian ZHANG; Zedong ZHENG; Xinli XIAO; Yuankang HE (Zhongguo dianli)
Power demand side management(DSM) has many advantages, including the optimization of power resource allocation, promoting energy conservation and emission reduction, realizing peak load shifting and renewable energy development, etc. However, under the current electricity market environment, there exists sever nonidentity between the cost of DSM and its expected profit, which may weaken the enthusiasm of power grid companies and terminal users. At the same time, the foremost motivation among governments, power grid companies and power users are different, which will lead to intense game. In order to better analyze the game behavior of the main participants, this paper focus on the politic environment of power demand side, and applies an dynamic evolutionary game model to analyze the game between the government and power companies, as well as the government and users. In addition, some measures of power demand side management are proposed to eliminate the restraint among power grid company and power users that caused by DSM, which is the future direction of this field.